Recurrent or familial facial palsy. Apropos of 6 cases and review of the literature - Benlyazid, A; Bassereau, G; Heitzmann, P; Foucault, N (Annales d'oto-laryngologie et de chirurgie cervico-faciale, 1995)
About 5 cases of recurrent facial palsy (1 case of familial récurrent facial palsy) and 1 case of non récurrent familial facial palsy, this work analyse the recent knowledges about this subject. Frequency of recurrent palsy is about 10% of the non traumatic facial palsies. A classification is proposed. The prognostic of a recurrence appears similar to the first palsy. Transmission of familial facial palsy seems autosomic dominant or multifactorial. Among the etiology, some like the alternobaric facial paralysis or Melkerson-Rosenthal syndrome could require special preventive or specific therapy.